Perlindungan Hukum Anak dari Perkawinan Adat Batak Toba yang Tidak Dicatatkan Ditinjau dari Hukum Keluarga dan Hukum Adat - Fiola Amabel Yohana Sinaga; Susilowati Suparto; Hazar Kusmayanti (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
This study examines the legal protection of children born from Toba Batak customary marriages that are not officially registered by the state. In Toba Batak customary law, a marriage is considered valid after all traditional ceremonies have been carried out, so that the child is recognized by the father's clan and social status within the customary community. However, state law requires marriage registration to ensure the certainty of the parents' legal status and the fulfillment of the child's civil rights. The absence of marriage registration has legal consequences in the form of limited recognition of the civil relationship between the child and the father, which impacts identity registration, access to public administration services, and the fulfillment of inheritance rights. This study uses a normative juridical method with analytical descriptive specifications through a review of laws and regulations, legal literature, and court decisions. The results show that preventive legal protection is realized through marriage registration to guarantee the child's right to identity. Meanwhile, repressive legal protection can be achieved through court decisions supported by valid evidence to confirm the child's legal status and ensure the fulfillment of their basic rights.